Leadership and culture in global hospitality industry - Seow, Han Yan (2008)
This study focuses on the relationship between cultural intelligence and leadership in the hospitality industry. It was found that CQ meta-cognition and CQ motivation have the highest significant correlation with leadership factors. It was also found that transformational leadership had the strongest causal relationship with cultural intelligence among all leadership factors. Finally, this study found that peers tend to give stricter ratings compared to bosses and subordinates. Peers were found to be the strictest in their ratings, while bosses and subordinates were similar in the strictness of their ratings.